2009
DOI: 10.1007/s11605-009-0823-9
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effect of Postoperative Complications on Oncologic Efficacy of R0 Pancreatectomy in Ductal Adenocarcinoma of the Pancreas

Abstract: Surgery-related major complication diminished the oncologic efficacy of R0 pancreatectomy. Margin-negative resection without major complication can enhance postoperative oncologic outcomes in ductal adenocarcinoma of the pancreas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 26 publications
2
14
1
Order By: Relevance
“…Accordingly, oncologic outcome is very poor, and left‐sided pancreatic cancer is regarded as one of the most difficult cancers to cure. Therefore, our current study suggests how important it is to reduce intraoperative transfusion in clinical oncology practices, as well as acquiring margin‐negative results and minimizing complications during pancreatectomy . Considering that reported blood transfusion rates in DP for pancreatic ductal carcinomas are approximately 30–40% , the observations in this study are important for improving oncologic outcome of left sided pancreatic cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, oncologic outcome is very poor, and left‐sided pancreatic cancer is regarded as one of the most difficult cancers to cure. Therefore, our current study suggests how important it is to reduce intraoperative transfusion in clinical oncology practices, as well as acquiring margin‐negative results and minimizing complications during pancreatectomy . Considering that reported blood transfusion rates in DP for pancreatic ductal carcinomas are approximately 30–40% , the observations in this study are important for improving oncologic outcome of left sided pancreatic cancer.…”
Section: Discussionmentioning
confidence: 82%
“…This is in contrast to that reported by Yeo et al in the 1990s, in which they showed that in addition to the tumour pathologic characteristics, the addition of reoperation had a negative impact on long-term survival of patients undergoing PD for periampullary carcinoma [30]. The detrimental effect of postoperative complications on the long-term survival of patients undergoing PD for pancreatic cancer has been a matter of controversy [31, 32]. In the present study-patients surviving the initial insult of early reoperations had similar long-term survival rates to those who did not undergo an early reoperation.…”
Section: Discussionmentioning
confidence: 93%
“…However, in our largest cohort of patients (i.e., those with pancreatic cancer), positive resection margin was not associated with poorer outcome. Whereas Kang et al observed that the rate of complications was higher with attempts at obtaining negative margins, which diminished the slim oncologic benefit of R0 resection, others have shown margin-negative resection to be predictive of survival 7,19. The lack of impact of R1 resection on overall survival in pancreatic cancer is not a unique finding.…”
Section: Discussionmentioning
confidence: 99%